Evolution of magnetic interactions in a pressure-induced Jahn-Teller driven magnetic dimensionality switch - Ghannadzadeh, S; Moeller, J; Goddard, P; Lancaster, T; Xiao, F; Blundell, S; Maisuradze, A; Khasanov, R; Manson, J; Tozer, S; Graf, D; Schlueter, J (2013)
We present the results of high-field magnetization and muon-spin relaxation measurements on the coordination polymer CuF2(H2O) 2(pyrazine) in pressures up to 22.5 kbar. We observe a transition from a quasi-two-dimensional to a quasi-one-dimensional antiferromagnetic phase at 9.1 kbar, driven by a rotation of the Jahn-Teller axis. Long-range antiferromagnetic ordering is seen in both regimes, as well as a phase separation in the critical pressure region. The magnetic dimensionality switching as pressure is increased is accompanied by a halving of the primary magnetic exchange energy J and a fivefold decrease in the ordering temperature TN. J decreases gradually with pressure in the two-dimensional phase, and then increases in the one-dimensional regime. We relate both effects to the changes in the crystal structure with applied pressure. © 2013 American Physical Society.